KEPENTINGAN INDONESIA MENGIMPOR KELAPA DARI THAILAND TAHUN 2014-2017 - Angga Mulia Prima Purba; Umi Oktyari Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Indonesia as the largest coconut producing country in the world is faced with a coconut production problem that has not been able to meet the supply needs of the domestic coconut processing industry. Lack of supply of raw materials that occurs due to low productivity of farmers' plantations and the revitalization of the coconut processing industry that occurs in Indonesia. The method used in this research is descriptive analytic method. The perspective used is the perspective of liberalism and uses reciprocal theory. This theory says that the actions of a country will be retaliated according to what has been done with the principle of applying justice. The occurrence of a shortage of supply of raw materials that occurred as a result of the export of coconut raw materials that occurred. This affects the fulfillment of the need for supply of raw materials for the domestic coconut processing industry. Based on the results of the analysis of the problems that occur, it can be concluded that Indonesia imports coconut from Thailand to fulfill the supply needs for the provision of raw materials and the quality of raw materials is better Keywords: Coconut, Import, Liberalism Perspective, Reciprocal Theory, Supply